LAYANAN APLIKASI GO-JEK: REALITAS MULTI AKAD DALAM TRANSAKSI JUAL BELI ONLINE GO-FOOD PERSPEKTIF EKONOMI ISLAM - Yuli Irawan Rasit; Rahman Ambo Masse; Muh. Irwan T.; Akram Ista (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
The rapid development of information technology can be seen from the massive use of the Internet network, which has also boosted the public's need to always carry out trade transactions using the Internet network. This is a challenge for Muslims to always be careful in transactions because Islam gives freedom to its followers in transactions but still places restrictions according to the Shari'a. Therefore, this study aims to find out the form of transactions in the go-food application and what the Islamic economic perspective is on these go-food transactions. The research method uses a qualitative interpretive approach. Sources of data come from primary data and secondary data and data collected using observation, interviews, and documentation. Respondents in this study were PT. Go-Jek, Go-Jek drivers, merchants, and consumers. This research focuses on the multiple contracts contained in Go-food services and the views of Islamic Economics on the transaction model. The results of this research show that it is true that there are multiple contracts in Go-food transactions because many parties are involved in them, including service leasing transactions between PT. Go-Jek and merchants, partners between PT. Go-Jek and drivers, as well as representative transactions between consumers and PT. Go-Jek and consumers with Go-Jek drivers. Islamic Economics views this transaction model resembles the forms of contracts in Islam, namely ijarah contracts, syirkah, wakalah bil ujrah, and their application does not conflict with Islamic Economics.